2018
DOI: 10.1044/2018_jslhr-h-18-0004
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing Middle Ear Pathology in 6- to 9-Month-Old Infants Using Wideband Absorbance: A Risk Prediction Model

Abstract: The risk prediction model had accurate discrimination and satisfactory calibration. Validation results indicate that it may generalize well to new infants. The model could potentially be used in diagnostic and screening settings. In the context of screening, probabilities provide an intuitive and flexible mechanism for setting the referral threshold that is sensitive to the costs associated with true and false-positive outcomes. In a diagnostic setting, predictions could be used to supplement visual inspection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
34
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(38 citation statements)
references
References 64 publications
4
34
0
Order By: Relevance
“…Early onset of otitis media in infancy increases risk of frequent and persistent infections through childhood (Howie, Ploussard, & Sloyer, 1975;MacIntyre et al, 2010;Marchant et al, 1986;Shurin, Pelton, Donner, & Klein, 1979). Quick and accurate tools for assessing middle ear function in infants could help provide timely diagnosis and appropriate management for affected children (Hunter et al, 2008b;Myers et al, 2018b). Wideband acoustic immittance (WAI) is an emerging test of middle ear function that is quick to administer and has several advantages over current routine clinical tests such as tympanometry.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Early onset of otitis media in infancy increases risk of frequent and persistent infections through childhood (Howie, Ploussard, & Sloyer, 1975;MacIntyre et al, 2010;Marchant et al, 1986;Shurin, Pelton, Donner, & Klein, 1979). Quick and accurate tools for assessing middle ear function in infants could help provide timely diagnosis and appropriate management for affected children (Hunter et al, 2008b;Myers et al, 2018b). Wideband acoustic immittance (WAI) is an emerging test of middle ear function that is quick to administer and has several advantages over current routine clinical tests such as tympanometry.…”
Section: Introductionmentioning
confidence: 99%
“…Although preliminary studies in infants have reported strong performance Myers et al, 2018b;Prieve et al, 2013b), more diagnostic research in this age group is necessary, as WAI could be a valuable tool for identifying middle ear pathology early in childhood. Furthermore, research is needed on different age groups through infancy, as there are large developmental effects on the WAI response that are not yet complete by 24 months of age (Keefe et al, 1993;Kei et al, 2013;Myers et al, 2019c).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations